Factors to Consider When Providing Audiological Services to People Who Have Hearing Loss and Their Communication Partners - Trychin, Samuel (Seminars in Hearing, 2012)
Hearing loss has a variety of psychosocial effects that often negatively affect those who have it and their communication partners. The negative effects are seen in peoples' attitudes toward hearing loss, compliance with treatment recommendations, and willingness to change communication behavior. One result is the tendency to blame the hearing aids for problems in understanding what others are saying when other factors are the real contributors to communication breakdowns. Educating patients and their communication partners about these hearing loss-related factors that interfere with getting the maximum benefits from hearing technology is a necessary step in effectively managing hearing loss.
Keywords: Human dynamics; psychosocial challenges; Ida Institute tools